ANALISIS KOMPETENSI PEDAGOGIK CALON GURU SEKOLAH DASAR DALAM MATA KULIAH MICROTEACHING - Niswati, Fadilah Ismiya; Sayekti, Ika Candra (Profesi Pendidikan Dasar, 2020)
This study aims were to describe: 1) pedagogical competencies mastery of student in Elementary School Teacher Education Department; 2) obstacles of pedagogical competencies faced by informant; 3) effort conducted by the informant to overcome the obstacles of pedagogical competencies. This is a qualitative study using descriptive methods. Data collection techniques used were observation, structured interviews and documentation. The results showed that 1) prospective teachers were able to master seven pedagogical of ten competencies, so the informant require to improve three other aspects, that are: curriculum development; implementation of educated learning; and effectively, empathically, and politely communication with students; 2) obstacles faced by informant are they haven’t mastered content material well; lack of creativity in media development; and they haven’t mastered classical management well; 3) efforts that required by the informant are by increasing knowledge about learning materials by finding references from various sources, increasing creativity in media development, and being able to be assertive and be able to reprimand students.